Time to sputum culture conversion and treatment outcome of patients with multidrug-resistant tuberculosis: a prospective cohort study from urban China. Issue 3 (23rd March 2017) - Lu, Peng; Liu, Qiao; Martinez, Leonardo; Yang, Haitao; Lu, Wei; Ding, Xiaoyan; Zhu, Limei
Sputum culture plays an important role in monitoring treatment response in patients with multidrug-resistant tuberculosis (MDR-TB), and sputum culture conversion is a clinical tool used to predict therapeutic efficacy [1]. Monthly culture monitoring is essential for earlier detection of treatment failure in patients with MDR-TB. More sensitive signals of nonresponse would further avoid adverse outcomes [2]. The timing of testing for culture conversion has potential as a marker of MDR-TB treatment success http://ow.ly/borO308pPXg